1996
DOI: 10.1002/(sici)1096-9098(199602)61:2<143::aid-jso10>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Male breast cancer: A retrospective study from a regional cancer center in northern India

Abstract: Over a 7‐year period from 1987 to 1993, 41 male breast cancer patients were seen in the breast cancer clinic of the Institute Rotary Cancer Hospital (IRCH) at the All India Institute of Medical Sciences (AIIMS). Their mean age was 54.2 years; and duration of symptoms ranged from 1 to 84 months with a mean of 15.1 months. Breast lump was the commonest presenting symptom. Fine needle aspiration cytology (FNAC) was the commonest diagnostic procedure. The TNM stage distribution was stage I, 5; stage II, 13; stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Consistent with previous literature 18,19 , the most common presentation was a painless sub-areolar lump detected in 87.9% of our patients. The most common location in women is the upper outer quadrant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous literature 18,19 , the most common presentation was a painless sub-areolar lump detected in 87.9% of our patients. The most common location in women is the upper outer quadrant.…”
Section: Discussionsupporting
confidence: 93%
“…Majority of MBCs are of infiltrating ductal histology 12 and are estrogen receptor positive. 17 Most commonly they present with lump in breast 18,19 with positive axillary nodes. 20,21 As in women, MBC survivorship is highly dependent on grade of tumors with grade 3 fairing much poorly than lower grades.…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of presentation is mostly in sixties but ranging from twenties to nineties. The duration of symptoms before diagnosis is declining [54] but there are major geographical differences ranging from a mean of 1-8 months [52,55,56] in western world to a mean of 12-15 months in the Asian-African continents and hence a later stage of presentation [57,58].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Previous reviews have reported that axillary node involvement was an important predictor of prognosis, and in some studies it has been the most important factor. 10,21,22 Other studies have found that the previously reported poor outcomes in male breast cancer patients were thought to arise from a delay in diagnosis, later treatment, and advanced stage at diagnosis. 10,15 A delay in diagnosis of 18 months has been previously reported.…”
Section: Commentmentioning
confidence: 99%